Tolerance Induction of Horse Allergy by Horse Contact with Curly Horses - Mitlehner, W.; Mitlehner, H. C. (Pneumologie, 2017)
A horse allergic rider completed 60 riding lessons on Curly Horses within six months. This rider has become clinically tolerant to normal horse breeds within this time. This case may indicate that riding and brushing ABCR Curly Horses after 60 riding hours facilitates tolerance induction. Our data indicate that this could be a valid alternative to the common recommendation to strictly avoid horse riding.